Number of Family Member and Previous Period Prices Affect Demand for Cayenne Pepper in Malang City - Rianti, Titis Surya Maha; Sari, Dina Kartika (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
Cayenne pepper is a crop that often experiences price fluctuations. The aim of this research is to determine the factors that influence the demand for cayenne pepper in Malang City. The research was conducted in Malang City using an observation sample of 70 respondents. Analysis was carried out using the multiple linear regression method. The research results show that the price of cayenne pepper in the previous period had an influence on demand for cayenne pepper. Apart from that, there is the influence of other factors such as the price of shallots, the price of red chilies, the number of family members and consumer tastes on the demand for cayenne peppers in Malang City. Seeing the high influence of prices on demand, of course the role of related parties is needed in maintaining the stability of food prices for strategic commodities in Indonesia.